2021
DOI: 10.1186/s12885-020-07746-9
|View full text |Cite
|
Sign up to set email alerts
|

Secondary endpoints analysis in patients with estrogen receptor-positive metastatic breast cancer treated with everolimus and exemestane enrolled in Oral Care-BC

Abstract: Background The Oral Care BC-trial reported that professional oral care (POC) reduces the incidence and severity of oral mucositis in patients receiving everolimus (EVE) and exemestane (EXE). However, the effect of POC on clinical response among patients receiving EVE and EXE was not established. We compared outcomes for estrogen receptor-positive metastatic breast cancer patients who received POC to those who had not, and evaluated clinical prognostic factors. All patients simultaneously receiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
(32 reference statements)
1
3
0
Order By: Relevance
“…However, studies adjusted at least for age, tumor stage, cancer treatment, and either comorbidities or smoking, on average, showed positive associations. Consistent positive associations were also observed among the secondary analysis of clinical trials 45 , 48 , 54 , 59 , 63 , 64 , 68 , 70 , 88 , 102 , 103 , 104 , 106 , 116 , 120 , 121 , 123 , 147 , 159 , 161 , 162 , 164 , 181 , 191 , 193 , 199 , 203 , 211 , 221 , 222 , 238 , 252 , 253 , 283 which were expected to have better treatment protocols and management. The evidence of greater body fatness causing increased mortality was unlikely to be caused solely by chance or bias, and was graded as strong probable evidence.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…However, studies adjusted at least for age, tumor stage, cancer treatment, and either comorbidities or smoking, on average, showed positive associations. Consistent positive associations were also observed among the secondary analysis of clinical trials 45 , 48 , 54 , 59 , 63 , 64 , 68 , 70 , 88 , 102 , 103 , 104 , 106 , 116 , 120 , 121 , 123 , 147 , 159 , 161 , 162 , 164 , 181 , 191 , 193 , 199 , 203 , 211 , 221 , 222 , 238 , 252 , 253 , 283 which were expected to have better treatment protocols and management. The evidence of greater body fatness causing increased mortality was unlikely to be caused solely by chance or bias, and was graded as strong probable evidence.…”
Section: Discussionsupporting
confidence: 62%
“…The meta‐analyses included 101 publications reporting postdiagnosis BMI (assessed from at‐diagnosis to on average 5.8 years postdiagnosis), waist circumference (at‐diagnosis to 7.9 years postdiagnosis), waist‐to‐hip ratio (at‐diagnosis to 2.5 years postdiagnosis) and pre‐ to postdiagnosis weight gain or loss (from 1 year before to 1 year or more after diagnosis) 27,39‐138 . In addition, 119 publications were descriptively synthesized…”
Section: Resultsmentioning
confidence: 99%
“…Both primary and secondary endpoints were analyzed as described previously ( 18 ). The accuracy of the TPM model was in ML-TPM setting was assessed as described previously ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…At present, the treatment options for RCC patients are very limited besides surgery [ 4 ]. It is reported that targeted biologics, such as tyrosine kinase inhibitor [ 5 ] and rapamycin inhibitor [ 6 ], have exhibited certain clinical efficacy for RCC. Nevertheless, these mentioned biologics easily produce drug resistance and negative adverse effects [ 7 ].…”
Section: Introductionmentioning
confidence: 99%